Is There Room for Targeting within Universalism? Finnish Social Assistance Recipients as Social Citizens - Saikkonen, Paula (2020)
This article focuses on the role of means-tested social assistance in Finland, which is often considered one of the Nordic welfare states described as having a universal welfare model. The article scrutinises the capacity of the final safety net to enhance the social citizenship of social assistance recipients. The Finnish social security system combines social insurance (earnings-related benefits), universal benefits (flat-rate benefits), free or affordable public services, and social assistance as a means-tested and targeted element, and thus it is a discussion on the degree of universalism that best captures the nature of universalism in the Finnish welfare state. Because the final safety net includes public services (especially social work) and income transfers (especially social assistance), its ability to strengthen social citizenship depends on both elements—separately and as a combination—as there may be a simultaneous need for financial aid and services. Whilst national registers provide data on social assistance, there is no national register data on municipal social services, which is why a survey was conducted. In this study, the heterogenic clients supported by the final safety net were described based on an open-ended question in the survey data. Statistics were then used to evaluate the frequency of client groups (capable clients, persistent clients, invisible clients, safety net dropouts). The article concludes that universalism as a social policy principle is challenged by the diversity of the clientele.